Properties of Concrete using Ferronickel Slag as Fine Aggregate - Saha, Ashish Kumer (Curtin University, 2018)
This study evaluated the use of by-product ferronickel slag as fine aggregate in concrete. It was found that mortar and concrete of good strength and durability could be produced by the combined use of ferronickel slag as a partial replacement of sand and fly ash as a partial replacement of cement. Leaching of metal ions from ferronickel slag were within acceptable limits. Thus, ferronickel slag can be a potential alternative fine aggregate for green concrete.